Analisis Pelaksanaan Bantuan Hukum kepada Masyarakat Miskin oleh Lembaga Bantuan Hukum PEKA Tuban (Studi Penelitian di Kecamatan Palang Kabupaten Tuban Jawa Timur) - Muhammad Ali Rofin; Ahmad Burhan Hakim; Ahmad Afan Zaini (Dikelola dan diterbitkan oleh Fakultas Syariah bekerja sama dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
Legal Aid Institutions have an important role in providing free legal aid, especially for the poor in undergoing the process in court, because the cost is not cheap when litigation. Therefore, it is necessary to know about the role of Legal Aid Institutions in providing legal aid for the poor, namely to provide justice rights for all communities, including the poor, because in the eyes of the law all are equal, how the poor always get the injustice they deserve. This thesis research on the Implementation of Legal Aid to the Poor by the Pejuang keadilan Legal Aid Institute Tuban uses a qualitative approach and an empirical normative legal approach, namely research that combines normative research and is supported by data or elements of empirical research, methods for data collection through observation,interviews and documentation. The research results obtained are as follows: all people can get free legal aid, there are no special requirements, only an identity card and a certificate of poverty, if any, This aid agency not only provides legitimacy but also non-legitimacy assistance. The obstacles faced in implementing legal aid are as follows: lack of public knowledge about legal aid, limited funds so that alternative routes use personal money, lack of support from the government for legal aid institutions that have not been accredited.